A feasibility study of fruit brandy production - Turk, Jernej (Agricultura (Maribor), 2002)
Fruit brandy production is considered as one of the very possibilities for home fruit processing. When considering to set up new farm business, the information regarding the economic feasibility o9f individual agricultural households should be obteinded by each farm entrepreneur. The simulation cost model for Slovene brandy production on the fruit farms is developed in this study. The break-even price and break-even yield were calculated for different kinds of fruit brandy. The sensitivity analysis was simultaneously conducted in order to determine the impact of different prices on the net financial result gained. The results show that home fruit brandy production could be economically feasible. The highest financial result was achived with plum brandy production, followed by pear brandy production and peach brandy production. Several aspects of tax legislation concerning the brandy production are also discussed here.
Keywords: žganje; žgane pijače; cene; proizvodnja